Performance and Usability of Three Systems for Continuous Glucose Monitoring in Direct Comparison. (September 2019) - Freckmann, Guido; Link, Manuela; Kamecke, Ulrike; Haug, Cornelia; Baumgartner, Bernhard; Weitgasser, Raimund
Background: To be able to compare continuous glucose monitoring (CGM) systems, they have to be worn in parallel by the same subjects. This study evaluated the performance and usability of three different CGM systems in direct comparison. Method: In this open, prospective study at two sites, 54 patients with diabetes wore three CGM systems each (Dexcom G5™ Mobile CGM system [DG5], Guardian™ Connect system [GC], and a Roche CGM system [RCGM]) in parallel for 6 or 7 days in a mixed inpatient and outpatient setting. Capillary comparison measurements were performed using a self-monitoring of blood glucose (SMBG) system. During study site visits, glucose excursions were induced. Performance of the systems was evaluated by calculating mean absolute relative differences (MARD, calculated as absolute differences for glucose concentrations <100 mg/dL and as relative differences for glucose concentrations ≥100 mg/dL), and mean relative differences (MRD, bias) between CGM and SMBG results. In addition, usability of the systems was assessed. Results: Overall MARD was 10.1 ± 2.1 for DG5, 11.5 ± 4.2 for GC, and 11.9 ± 5.6 for RCGM. Performance improved in all systems after the first day of use. All systems showed >99% of values within zones A and B of the consensus error grid. Overall, all CGM systems showed a small negative bias compared to SMBG. Usability of the systems differed regarding patch adhesion rate, failure rate, and patient rating. Most patients preferred GC, but in general all systems were rated positively. Conclusion: All three CGM systems showed similar overall accuracy in this direct comparison, but small differences were observed with regard to specific glucose ranges and usability aspects.